LGG-21. MR-GUIDED LASER INTERSTITIAL THERMAL THERAPY FOR UNRESECTABLE AND SYMPTOMATIC PEDIATRIC LOW GRADE GLIOMA. (4th December 2020) - Kram, David; Benjamin-Eze, Jessica; Strowd, Roy; Tatter, Stephen
Abstract: BACKGROUND: Pediatric low-grade gliomas (LGG) not amenable to resection, while often indolent, represent a significant source of cancer-related morbidity and an unmet therapeutic need. Standardly, these patients are treated with sequential lines of chemotherapy, while delaying as long as possible radiation. Magnetic resonance-guided laser interstitial therapy (LITT) is a minimally invasive procedure that utilizes real-time MR thermography to ablate brain lesions. METHODS: A 15-year-old girl was diagnosed with a suprasellar, hypothalamic LGG, BRAF V600E mutation positive. The tumor was unresectable, and due to progressive vision loss and headaches, the patient underwent treatment. Despite sequential trials of thioguanine/procarbazine/lomustine/vincristine, carboplatin/vincristine, dabrafenib, and combination dabrafenib/trametinib, the patient continued to experience debilitating headaches, malnutrition, school absenteeism, and overall poor quality-of-life. Using real-time, sequential MRI-thermometry and the Neuroblate cooled directional laser catheter, the bulk of the enhancing tumor was heated to a killing temperature. RESULTS: At 1-year post LITT, the patient's symptoms were dramatically improved, including greatly improved headaches, malnutrition, school absenteeism, and overall quality of life. LITT was generally well tolerated, though the patient had slight progressive left homonymous hemianopia, thought secondary to LITT impact on the optic tracts. The tumor progressively shrank over the year post-LITT to a peak of 42% volume reduction. CONCLUSION: We report a case of a pediatric patient with an unresectable low grade glioma who underwent LITT with excellent clinical and radiographic effects. LITT should be considered for children with unresectable and morbid LGGs that fail to respond to more conventional therapies.